2009
DOI: 10.1158/1078-0432.ccr-08-2729
|View full text |Cite
|
Sign up to set email alerts
|

Limited Amounts of Dendritic Cells Migrate into the T-Cell Area of Lymph Nodes but Have High Immune Activating Potential in Melanoma Patients

Abstract: Purpose: The success of immunotherapy with dendritic cells (DC) to treat cancer is dependent on effective migration to the lymph nodes and subsequent activation of antigen-specificTcells. In this study, we investigated the fate of DC after intradermal (i.d.) or intranodal (i.n.) administration and the consequences for the immune activating potential of DC vaccines in melanoma patients. Experimental Design: DC were i.d. or i.n. administered to 25 patients with metastatic melanoma scheduled for regional lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
189
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(194 citation statements)
references
References 28 publications
5
189
0
Order By: Relevance
“…These are both transcriptionally and functionally different to BDC and fail to migrate after injection to draining LNs, despite various manipulations to correct this deficit. 31,32 Given the potential of therapeutic DC vaccination for treating hematological and other malignancies, there is merit in investigating the postulated advantages of using primary BDC as an alternative to Mo-DC. 1 Initial clinical studies have shown that immune selected BDC preparations are safe and able to induce clinical responses in patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These are both transcriptionally and functionally different to BDC and fail to migrate after injection to draining LNs, despite various manipulations to correct this deficit. 31,32 Given the potential of therapeutic DC vaccination for treating hematological and other malignancies, there is merit in investigating the postulated advantages of using primary BDC as an alternative to Mo-DC. 1 Initial clinical studies have shown that immune selected BDC preparations are safe and able to induce clinical responses in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Limited numbers of Mo-DC drain to the LN 24 h after injection and the vast majority remain at the site of injection. 31,32 Thus, we were particularly interested in how CMRF-56 C BDC migrated and whether their transfection with IVT-mRNA impacted this. The unique potential of BDC was once again emphasized by their specific migration to the LN homing chemokine CCL21, whereas there was little response by other APC, notably B cells and monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations